2019
DOI: 10.12911/22998993/109859
|View full text |Cite
|
Sign up to set email alerts
|

The Water Needs of Grapevines in the Different Regions of Poland

Abstract: The aim of this study was to estimate the water needs of grapevines (Vitis vinifera L.) in the different regions of Poland. The requirements of grapevines water, considered as the crop evapotranspiration, were determined using the plant coefficient method. The grapevine plants crop evapotranspiration was measured using the reference evapotranspiration and plant coefficients. The plant coefficients were adapted to the reference evapotranspiration that was calculated using the Blaney-Criddle's formula, modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…In turn, Pardo et al [27] recorded the seasonal water consumption of asparagus under lysimeter conditions ranging from 274 mm to 294 mm. In the latest research on asparagus water needs in various regions of Poland reported by Rolbiecki et al [28], the irrigation needs of asparagus plants were found to be, on average, 228 mm in the period from July 1 to August 31 in the central-north-west region of Poland, which also covers the area considered in the present study. The total water needs of asparagus in the postharvest period were higher in the first year of the study (258 mm) than in the second year of the study (241 mm) (Figure 3).…”
Section: Irrigation Needssupporting
confidence: 69%
“…In turn, Pardo et al [27] recorded the seasonal water consumption of asparagus under lysimeter conditions ranging from 274 mm to 294 mm. In the latest research on asparagus water needs in various regions of Poland reported by Rolbiecki et al [28], the irrigation needs of asparagus plants were found to be, on average, 228 mm in the period from July 1 to August 31 in the central-north-west region of Poland, which also covers the area considered in the present study. The total water needs of asparagus in the postharvest period were higher in the first year of the study (258 mm) than in the second year of the study (241 mm) (Figure 3).…”
Section: Irrigation Needssupporting
confidence: 69%
“…Therefore, in Poland, to obtain favorable quality parameters of grapevine fruits, it is recommended to finish the irrigation of vineyards 25-30 days before harvest [28]. In the studied provinces of western Poland, the sums of rainfall in September were relatively low compared to the eastern provinces studied by Rolbiecki et al [21]. In current research, the sum of precipitation in September in the provinces of western Poland ranged from 43 to 45 mm.…”
Section: Discussionmentioning
confidence: 57%
“…An assessment of the water needs of vineyards located in the western provinces of Poland, based on a period of thirty years (1981-2010), showed a clear tendency to increase the water needs of the grapevines, both in the growing season (May-October) and during the period of increased water needs of plants (June-August) and in July, when the water needs of plants are usually the highest. Research published by Rolbiecki et al [21] showed that in 1981-2010 the water needs of grapevines increased also in other regions of Poland, especially in south-eastern Poland, by as much as 7.6 mm per decade. The increase in water needs of the grapevines in the provinces of western Poland is probably caused by a significant increase in air temperature, which is the result of global warming, observed particularly in the last two decades of the 20th century [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research published by Rolbiecki, et al [23] the water needs of asparagus are the highest in the last two months of the irrigation season, i.e., July and August (from 3.2 mm to 4.4 mm, daily). In the research on asparagus water needs in various regions of Poland, reported by Rolbiecki et al [24], it was calculated that the irrigation requirements of asparagus plants are on average 228 mm in the period from 1 July to 31 August in the centralnorthwest region of Poland, which also covers the area considered in the present study. In the previous study [10], water requirements of asparagus under drip irrigation ranged from 205 mm to 272 mm in the individual years.…”
Section: Meteorological Conditionsmentioning
confidence: 57%